On Time Scales Fractional Volterra-Fredholm Integro-Differential Equation - Hamoud, Ahmed A.; Ghadle, Amol D. Khandagale; Kirtiwant P. (Discontinuity, Nonlinearity, and Complexity, 2026)
The existence, uniqueness, and Ulam-Hyers stability of the Volterra-Fredholm integro-differential equation with non-instantaneous impulses and periodic boundary conditions over time scales are investigated in this paper using Banach fixed point theorems and Caputo delta fractional derivative. Finally, we present an example to confirm our main findings.